Colombia - Morrison, Marion (Chicago : Children's Press, 1990)
Describes the geography, history, people, industries, and culture of Colombia.
Includes index.
6.
7.7
5-8
5-9.
Keywords: Colombia -- Description and travel -- Juvenile literature; Colombia -- History -- Juvenile Literature; Colombia; Colombia